ANALISIS KEWENANGAN MAHKAMAH KONSTITUSI DALAM MEMBUAT PUTUSAN YANG BERSIFAT POSITIVE LEGISLATURE - Jadmiko, Jadmiko; Iswari, Dyah (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2017)
This article aims to analyze the authority of the constitutional court as a judicial institution in issuing a decision that is a positive legislature to study the Constitutional Court's Decision Number 102 / PUU-VII / 2009. Constitutional Court in conducting judicial authority acting as a norm eraser. This research is a normative prescriptive. The research’s results indicate that the Constitutional Court’s Decision Number 102 / PUU-VII / 2009 is one type of decision that is a positive legislature issued by the Constitutional Court. Of the Constitutional Court’s Decision Number 102 / PUU-VII / 2009, the positive legislature lies in the ruling that declared, the provisions of an article examined is constitutional if accordance with what is intended by the Constitutional Court. A decision with the interpretation as a positive legislature made by the Constitutional Court aims to avoid a legal vacuum.